2009
DOI: 10.1080/03009730902990453
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two visual angiographic perfusion grades in acute myocardial infarction

Abstract: IntroductionPrognosis after opening the obstructed coronary artery in acute myocardial infarction (AMI) is influenced by several factors. In routine clinical practice, revascularization is considered to be successful when the restoration of epicardial blood-flow is complete. However, the patent epicardial artery does not always provide functional recovery in the myocardium. There are two visual angiographic grades to assess myocardial perfusion: myocardial blush grade (MBG) and TIMI myocardial perfusion grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A relatively weak (r = 0.24) but significant correlation between TMPG and summed relative ST segment resolution was seen after thrombolytic treatment [11]. A better correlation (r = 0.58) was reported between TMPG and relative ST segment resolution in a single lead in patients treated invasively [12]. Other authors showed significantly more frequent occurrence of more than 50% ST segment resolution after pPCI in patients with TMPG 2 or 3 [13].…”
Section: Discussionmentioning
confidence: 99%
“…A relatively weak (r = 0.24) but significant correlation between TMPG and summed relative ST segment resolution was seen after thrombolytic treatment [11]. A better correlation (r = 0.58) was reported between TMPG and relative ST segment resolution in a single lead in patients treated invasively [12]. Other authors showed significantly more frequent occurrence of more than 50% ST segment resolution after pPCI in patients with TMPG 2 or 3 [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bertomeu--Gonzalez et al [10] have raised the question on inter-observer variability of MBG assessment, have reported on a lack of correlation between MBG and LVEF assessed with magnetic resonance imaging (MRI). Authors of additional studies point out superior performance of TIMI myocardial perfusion scale (TMP) over MBG in correlation with other indices of myocardial perfusion [1,11].…”
Section: Introductionmentioning
confidence: 99%